Unconsoled. (Economist, 2019)
The article focuses on cloud computing in the video-gaming business. Topics discussed include Project xCloud, Microsoft's foray into cloud gaming, goal of cloud gaming, Stadia, Google's cloud-gaming product, outlook for cloud gaming and the use of cloud computing for tricky calculations that are also relatively insensitive to small delays.